Modular Concept and Optimization of PCMSR 250 MWe Turbine Module - Harto, Andang Widi (2014)
ABSTRACT Passive Compact Molten Salt Reactor (PCMSR) is a modular advanced nuclear reactor type. The PCMSR uses liquid fuel (molten fluoride salt) and solid graphite moderator. The PCMSR is designed as a thermal breeder reactor, thus the fuel consumption is very efficient and the amount of radioactive waste is reduced significantly. Another important features of PCMSR are inherently safe, totally passive safety system and economic. For cost reduction, PCMSR applies the concept of simplicity and modularity. PCMSR design consists of reactor module, turbine module and fuel management module. The turbine module is a regenerative multi stage Brayton cycle consists of four stages turbine and heater, four stages compressor and cooler plus one stage regenerator. The maximum temperature operation is 1323 K (1150 ºC) and minimum temperature operation is 333 K (60 ºK). The turbine system performance analysis will be performed by calculating overall turbine system efficiency. This will be calculated using formula derived from thermodynamics multistage regenerative Brayton cycle. For the optimum design, more detail heat transfer calculation will be performed for heat transfer equipment, i.e. heaters, coolers and regenerator. Overall efficiency calculation shows that the maximum efficiency is 56 % at optimum turbine pressure ratio of 4.3 for 4 stages turbine and 4 stages compressor. The isentropic efficiency of turbines and compressors are 93 % and 88 % respectively. The same value of heat transfer capability is designed for all heaters and compressors. Heat transfer calculation shoes that the active length of the heaters and the coolers are approximately the same, i.e. 5 m. The active length of recuperator is 11.2 m. With these sizes of the heaters, coolers and recuperators, the estimated total length of the turbine module is roughly 20 m. With these sizes, the turbine module can be completely fabricated in a workshop, transported and erected to power plant site.